Graphene Oxide Quantum Dots Promote Osteogenic Differentiation of Stem Cells from Human Exfoliated Deciduous Teeth via the Wnt/β-Catenin Signaling Pathway. (9th February 2021) - Yang, Xin; Zhao, Qi; Chen, JingWen; Liu, Jiayue; Lin, Jiacheng; Lu, Jiaxuan; Li, Wenqing; Yu, Dongsheng; Zhao, Wei
Abstract : Graphene oxide quantum dots (GOQDs) are a carbon nanomaterial with broad potential for application in the field of nanomaterial biomedicine. Stem cells from human exfoliated deciduous teeth (SHEDs) play an important role in tissue engineering and regenerative medicine. This study investigated the effects of GOQDs on SHED osteogenic differentiation. GOQDs were synthesized; then, the proliferation of SHEDs incubated in GOQDs at different concentrations was evaluated; and the live cells were observed. We observed that live SHEDs incubated in GOQDs emitted green fluorescence in the absence of chemical dyes, and 1, 10, and 50 μ g/mL GOQDs significantly promoted SHED proliferation. Culture with the osteogenic induction medium containing 10 μ g/mL GOQDs induced calcium nodule formation, increased alkaline phosphatase (ALP) activity, and upregulated SHED mRNA and protein levels of OCN, RUNX2, COL I, and β -catenin. With the addition of Dickkopf 1 (DKK-1) or β - catenin knockdown, expression levels of the above mRNAs and proteins were decreased in GOQD-treated SHEDs. In summary, at a concentration of 10 μ g/mL, GOQDs promote SHED proliferation and osteogenic differentiation via the Wnt/ β -catenin signaling pathway. This work provides new ideas and fundamental information on interactions between GOQDs and SHEDs that are relevant for the biomedical engineering field.